A note on the occurrence of sperm whales (Physeter macrocephalus) off Peru, 1995-2002 - Garcia-Godos , Ignacio (J. Cetacean Res. Manage., 2023)
Thirty-eight sightings of sperm whales (Physeter macrocephalus) were recorded off Peru (3-18°S) during 21 surveys conducted aboard platforms of opportunity, 1995-2002, with a search effort of 33,407 nautical miles of observation. Two main areas of concentration were detected: northern Peru (19 sightings) and southern Peru (16 sightings). Almost 58% of sightings occurred during the same or consecutive days. Group size ranged 1-18 individuals, with a mean of 3.5 (SD=3.9). The modal group size was one, accounting for 36.8% of sightings. Groups of three or more individuals accounted for 39.5%. An important increase in sightings occurred between 2001 and 2002, accounting for 68% of the records and suggesting migration into Peruvian waters from other regions. Positive correlations between indices of relative abundance and the anomaly of sea surface temperature were found, although warm events such as El Niño increased the uncertainty in sighting rates, reducing correlation values. The positive relationship between indices of relative abundance and commercial catch per unit effort for the squid Dosidicus gigas suggests some degree of interaction, although the extent of the role of this squid in the diet of sperm whales in the area requires further study